Remarks by World Bank Group President David Malpass at the Virtual COVID-19 Global Action Plan Foreign Ministerial Meeting - Malpass, David (World Bank, Washington, DC, 2022)
These remarks were delivered by World Bank Group President David Malpass at the Virtual COVID-19 Global Action Plan Foreign Ministerial Meeting on July 19, 2022. He said that Coronavirus (COVID-19) has highlighted the pressing need for action to build stronger health systems and mobilize additional resources for Pandemic Prevention, Preparedness, and Response or PPR. He mentioned that when COVID-19 struck, it required immediate support for developing countries, and the World Bank Group mounted the fastest and largest response in our history with operations in over 100 countries. He declared that the World Bank Group is working closely with the COVID-19 Vaccine Delivery Partnership to support focus countries to achieve their coverage goals. He said that they have worked closely with the WHO, IMF, and WTO throughout the pandemic. He also added that they have also worked with other development partners, including USAID and JICA, to strengthen the laboratory capacity of regional entities, such as the Africa CDC. He mentioned that the World Bank Group is proceeding quickly to establish a financial intermediary fund or FIF to mobilize additional resources for PPR and complement efforts to strengthen health systems in developing countries and regions. He concluded by saying that they look forward to more countries joining this partnership, to strengthening health systems further, and to working together on this critical agenda, including at the Tokyo International Conference on African Development (TICAD) in August in Tunisia.